2019
DOI: 10.1039/c8ra10338k
|View full text |Cite
|
Sign up to set email alerts
|

Novel cathepsin K inhibitors block osteoclasts in vitro and increase spinal bone density in zebrafish

Abstract: Cathepsin K (Cat K) is a predominant cysteine protease and highly potent collagenase expressed in osteoclasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In recent years, CTSK inhibitors have been developed by pharmaceutical companies as potential anti-resorptive agents ( Dai et al, 2020 ). The pharmacological effects of CTSK inhibitors on osteoporosis have been demonstrated in zebrafish, rodent models, and humans ( Stoch and Wagner, 2008 ; Xue et al, 2019 ). In this study, the cell-free CTSK enzymatic assay revealed that 10-gingerol possessed CTSK inhibition ability ( Figure 4H ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, CTSK inhibitors have been developed by pharmaceutical companies as potential anti-resorptive agents ( Dai et al, 2020 ). The pharmacological effects of CTSK inhibitors on osteoporosis have been demonstrated in zebrafish, rodent models, and humans ( Stoch and Wagner, 2008 ; Xue et al, 2019 ). In this study, the cell-free CTSK enzymatic assay revealed that 10-gingerol possessed CTSK inhibition ability ( Figure 4H ).…”
Section: Discussionmentioning
confidence: 99%
“…CTSK is secreted from the lysosomes of mature osteoclasts and interacts with the E3 ubiquitin ligase Cb1 (Tyr737) adaptor protein and the PI3K p85 regulatory subunit [ 75 ]. A22, a specific potent inhibitor of CTSK, blocked osteoclast activation in vitro and enhanced the spine bone density in zebrafish [ 76 ]. In clinical tests, a series of pharmaceutical products were applied to inhibit CTSK activity, such as balicatib (AAE581), ONO-5534, and odanacatib, which were mostly efficacious for inhibiting osteoclast bone resorption and preventing bone loss.…”
Section: Master Regulators Of Osteoclastogenesismentioning
confidence: 99%
“…Meanwhile, several Cat-K inhibitors are currently being studied in clinical trials for the treatment of osteomalacia, osteoporosis, and MBDs ( Lu et al , 2018 ). Odanacatib, an extremely selective and recoverable Cat-K inhibitor, is currently in phase 3 trials ( Xue et al , 2019 ). In phase II clinical trials, it reduced bone resorption, while only temporarily inhibiting bone formation, and its use for five years resulted in significant sequential increases in bone density at the hip and spine ( Lu et al , 2018 ).…”
Section: Problems and Significant Improvements In Drug Therapymentioning
confidence: 99%